Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Citra Merek Pada Kepuasan Pelanggan di Youo Resto Hotel Zia Sanno Pluit - Debora Angela Ctistie Senduk; Bambang Nur Supriyanto (Human Capital Development, 2023)
This study aims to investigate how products, services, and brand image, on customer satisfaction at Youo Resto Hotel Zia Sanno Pluit. Customers who visit Youo Resto Hotel Zia Sanno Pluit are the population of this study, which uses primary data in the form of questionnaires filled out by 100 respondents. In this study, researchers used random sampling as a sampling method. Multiple linear regression models and data analysis methods such as descriptive statistical analysis and parametric statistical analysis are used in quantitative research methods. The results of the study can be concluded that product has a significant effect on customer satisfaction, service has a significant effect on customer satisfaction, and brand image has a significant effect on customer satisfaction.